Possibilidades de intervenção e de desenvolvimento urbanos em área de assentamento espontâneo no contexto metropolitano de Belém: o caso do Paracuri 3 - ABRAHÃO, Omar Numa (2008)
In this work we analyze strategies for urban development in areas of spontaneous human settlement, considering the theoretical conceptions of habitation, urban space and urban development, which are fundamental for inhabitants and urban technicians, for planning urban development of segregated areas. This analysis is based on studies using as reference the urban occupation Paracuri 3, situated in Icoaraci District, Belém City, State of Pará. The methodology is composed by bibliographic research, direct observation of the studied area and application of a semi-structured questionnaire to urban technicians and inhabitants of the researched area. Considering the experiences of inhabitants of the area and the conceptions of the urban technicians - who knows the researched area or have already worked there - we detected a social tension and different development strategies in these conceptions.